Proceso de atención de enfermería en un paciente con malaria - Carpio Valdiviezo, Oscar Andres (Machala : Universidad Técnica de Machala, 2020)
Malaria is a disease caused by protozoa of the genus Plasmodium (falciparum, ovale, vivax and malariae) and transmitted by the bite of the female Anopheles mosquito. At present, malaria is still considered a disease of great impact, since we must remember that there is a population that resides in areas where it is common to find it, this being a public health problem worldwide, 228 million cases are reported in all the world. The African Region accounts for a disproportionately high share of the global burden of disease. In 2018, 93% of malaria cases and 94% of deaths from this disease were reported in the region. This work was carried out with the objective of developing a care plan for the patient with Malaria in accordance with the NANDA taxonomy. Health personnel must provide educational talks to the population for the elimination of mosquitoes that transmit malaria, however, one of the most essential tasks is the organization with the local health committee, for the identification and elimination of breeding sites. mosquitoes.
El paludismo es una enfermedad causada por protozoos del género Plasmodium y transmitida por la picadura de la hembra del mosquito Anopheles. En la actualidad el paludismo sigue considerado como una enfermedad de gran impacto, pues debemos de recordar que hay población que reside en áreas donde es común encontrarlo, siendo este un problema de salud pública a nivel mundial, se reportan 228 millones de casos en todo el mundo. En la Región de África se registra una parte desproporcionadamente alta de la carga mundial de la enfermedad. En 2018 se informa que existe en la región el 93% de los casos de paludismo y el 94% de las defunciones por esta enfermedad. Este trabajo se realizó con el objetivo de elaborar un plan de cuidados para paciente con Malaria de acuerdo con la taxonomía NANDA. El personal de salud debe brindar charlas educativas a la población para la eliminación de los mosquitos que transmiten la malaria, sin embargo, una de las tareas más primordiales es la organización con el comité local de salud, para la identificación y eliminación de los criaderos de mosquitos.
Keywords: MALARIA, PLASMODIUM; PALUDISMO; ENFERMEDAD; POBLACION